Comparison of disaster management practices in Indonesia: a study of resilience in Garut and Majene districts - Ulfiah Syukri; Nandang Alamsah Deliarnoor; Ida Widianingsih (Discover Sustainability)
Abstract As natural disasters occur with increasing frequency, disaster management in Indonesia is becoming an increasingly urgent concern. This paper analyzes the disaster management and mitigation strategies employed in Majene Regency and Garut Regency. The qualitative methodology encompasses interviews, document analysis, and the investigation of certain critical facts. Furthermore, we employed NVivo 12 Plus to illustrate the thematic analysis. The findings indicate that Majene and Garut have implemented disaster management strategies encompassing community activities and municipal regulations. The lack of comprehensive catastrophe insurance, encompassing both private and public sector coverage, coupled with insufficient administrative skills and resources, constitutes the primary barriers to successful mitigation. Logistical and accessibility challenges in remote areas considerably impeded the evacuation and relief distribution efforts throughout the response phase. Focusing on debris clearance, rehabilitation, and economic and psychological empowerment, post-disaster recovery in both regions highlighted the importance of collaboration among government agencies, NGOs, the corporate sector, and communities. This research enhances disaster management literature by advocating for community preparedness, improving inter-agency collaboration, and instituting disaster insurance to augment future disaster management effectiveness. These findings align with disaster management ideas and practices that stress the need for teamwork across different sectors to strengthen community resilience against disasters.